Trends in serum total cholesterol and dietary fat intakes in New Zealand between 1989 and 2009 - Jody C. Miller; Claire Smith; Sheila M. Williams; Jim I. Mann; Rachel C. Brown; Winsome R. Parnell; C. Murray Skeaff (Elsevier, 2016)
Abstract Objective: To describe trends in serum cholesterol and dietary fat intakes for New Zealand adults between 1989 and 2008/09. Methods: Serum total cholesterol concentrations and dietary fat intakes were analysed for 9,346 New Zealanders aged 15-98 years (52% women) who participated in three national surveys in 1989, 1997 and 2008/09. Results: Population mean serum cholesterol decreased from 6.15 mmol/L in 1989 to 5.39 mmol/L in 2008/09. Mean saturated fat intake decreased from 15.9% of energy intake in 1989 to 13.1% in 2008/09. Between 1997 and 2008/09, unsaturated fat intake increased and fat from butter and milk decreased. Older adults had the largest decrease in serum cholesterol (1.35 mmol/L). Conclusions: The decrease in serum cholesterol is substantially larger than reported for many other high‐income countries, and occurred in parallel with changes in dietary fat intakes and, for older adults, increased use of cholesterol‐lowering medications. Implication: Given the demonstrated role of reduced saturated fat intake on lowering serum cholesterol, and as population average serum cholesterol levels and saturated fat intakes exceed recommended levels, initiatives to further encourage reductions in saturated fat are imperative.